Case report of traumatic intrapericardial diaphragmatic hernia: Laparoscopic composite mesh repair and literature review. (2020) - Aborajooh, Emad A.; Al-Hamid, Zaid
Highlights: Post-traumatic rupture of the diaphragm with herniation of abdominal viscera into the pericardium is a rare injury. Delayed diagnosis of Intrapericardial diaphragmatic hernia does not preclude laparoscopic repair. Repair of large defect with composite mesh reduces the risk of adhesions, infection and erosion of nearby viscera. Abstract: Introduction: Traumatic rupture of the diaphragm with herniation of abdominal viscera into the pericardium is a rare injury. We present a case of intrapericardial diaphragmatic hernia after one year of thoracoabdominal trauma. This case is the 106th in the literature and only the fifth treated by the laparoscopic approach including this case. After case presentation, we will discuss post-traumatic intrapericardial diaphragmatic hernias by reviewing the literature. Case presentation: A 48-year-old male presented to our outpatient clinic with a history of thoracoabdominal trauma due to a motor vehicle accident one year ago. The patient complained from abdominal pain and constipation over the last year. After a thorough history and physical examination, thoracoabdominal computed tomography (CT) was performed. The CT scan revealed herniation of the transverse colon and omentum through a large anterior diaphragmatic defect into the pericardial sac. Laparoscopic composite mesh repair was done. The patient had an uneventful postoperative course and was discharged home on the second postoperative day. The patient was asymptomatic at regular follow-up six months postoperatively. Conclusion: Late presentation of intrapericardial diaphragmatic hernia is rare. Chest computed tomography is the most useful diagnostic tool. Delayed diagnosis of Intrapericardial diaphragmatic hernia does not preclude laparoscopic repair by primary closure or with mesh according to the size of the defect.